Dampak Teknologi dalam Pembentukan Karakter Gen Alpha - Zendrato, Juwita Febri Cahyani; Ziliwu, Noel Michael Putra (CV. SINAR HOWUHOWU, 2025)
This study aims to examine the impact of digital technology on character development among Generation Alpha, focusing on both positive and negative aspects in Bawodesolo Village. A qualitative descriptive approach is employed to analyze in-depth how digital technology influences this generation’s character formation. Data were gathered through interviews and observations involving 10 children actively using digital devices in their daily lives. The results reveal that digital technology offers positive impacts, such as enhancing digital literacy, creativity, and independent learning skills. However, adverse effects are also evident, including digital addiction, diminished social interaction, and exposure to inappropriate content. These findings suggest a complex influence where technology both facilitates and impedes social and emotional growth. Thus, the role of parents and educators is crucial in managing technology use to foster positive character development in Generation Alpha. Appropriate supervision and content selection are recommended to maximize benefits while minimizing potential harms.